THE EFFECT OF DISCOVERY LEARNING MODEL WITH MULTIMEDIA AND CREATIVITIES TO STUDENTS LEARNING OUTCOMES - Jeperis Nahampun (Universitas Negeri Medan, 2014)
This research aims to analyzed (1) the difference between students the learning outcomes of students who were taught physics using Discovery Learning Model with multimedia and Direct Instruction Model. (2) The difference between physics students learning outcomes in the group that have low and high creativity. (3) Interaction creativity level who were taught using Discovery Learning Model with multimedia and Direct Instruction Model on learning outcomes of physics. This research was a quasi experiment. The population of this research was a student os class X MIA SMAN 5 Medan of the academic year 2013/2014. Sampling technique using a cluster random sampling consisting of two classes with 46 samples for the control class and 45 samples for the experiment class. The instrument of this research is in form of test learning result and creativity test. The technique used to analyze the data is the two way Varian of analysis. Based on the results of data processing, concluded that (1) there was a significant difference between the student achievement taught with discovery learning model with multimedia and those were taught with direct instruction model. (2) There was a significant difference between student achievement that has high creativity and low creativity. (3) There was a significant interaction between discovery learning model and direct instruction with the creativity level toward students’ achievement of physics.